Development of the chronic obstructive pulmonary disease morning symptom diary (COPD-MSD). Issue 1 (December 2016) - Globe, Gary; Currie, Brooke; Leidy, Nancy; Jones, Paul; Mannino, David; Martinez, Fernando; Klekotka, Paul; O'Quinn, Sean; Karlsson, Niklas; Wiklund, Ingela
Abstract Background The morning tends to be the most difficult time of day for many patients with chronic obstructive pulmonary disease (COPD) when symptoms can limit one's ability to perform even simple activities. Morning symptoms have been linked to higher levels of work absenteeism, thereby increasing the already substantial economic burden associated with COPD. A validated patient-reported outcome (PRO) instrument designed to capture morning symptoms will allow for a more comprehensive approach to the evaluation of treatment benefit in COPD clinical trials. Methods A qualitative interview study was conducted among a sample of symptomatic adults with COPD. Concept elicitation interviews (n = 35) were conducted to identify COPD morning symptoms, followed by cognitive interviews (n = 21) to ensure patient comprehension of the items, instructions and response options of the draft COPD Morning Symptom Diary (COPD-MSD). All interview transcript data were coded using ATLAS.ti software for content analysis. Results Mean age of the concept elicitation and cognitive interview sample was 65.0 years (±7.5) and 62.3 years (±8.3), respectively. The study sample represented the full range of COPD severity (Global Initiative for Chronic Lung Disease [GOLD] classifications I–IV) and included a mix of racial backgrounds, employment status and educational achievement. During the concept elicitation interviews, the three most frequently reported morning symptoms were shortness of breath (n = 35/35; 100 %), phlegm/mucus (n = 31/35; 88.6 %), and cough (n = 30/35; 85.7 %). A group of clinical and instrument development experts convened to review the concept elicitation data and develop the initial 32-item draft COPD-MSD. Cognitive interviews indicated subjects found the draft COPD-MSD to be comprehensive, clear, and easy to understand. The COPD-MSD underwent minor editorial revisions and streamlining based on cognitive interviews and input from the experts to yield the final 19-item daily diary. Conclusions This study supports the content validity of the new COPD-MSD and positions the diary for quantitative psychometric testing.